2019
DOI: 10.3847/1538-4357/ab1010
|View full text |Cite
|
Sign up to set email alerts
|

Alignment between Filaments and Galaxy Spins from the MaNGA Integral-field Survey

Abstract: Halos and galaxies acquire their angular momentum during the collapse of surrounding large-scale structure. This process imprints alignments between galaxy spins and nearby filaments and sheets. Low mass halos grow by accretion onto filaments, aligning their spins with the filaments, whereas high mass halos grow by mergers along filaments, generating spins perpendicular to the filament. We search for this alignment signal using filaments identified with the "Cosmic Web Reconstruction" algorithm applied to the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
65
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 91 publications
4
65
0
1
Order By: Relevance
“…The mass dependence of the spin alignment signal is however debated. While some works confirmed the existence of a galaxy spin transi- tion from parallel to perpendicular with respect to the filament's direction (Dubois et al 2014;Codis et al 2018;Kraljic et al 2020b), and analogously with respect to walls (Codis et al 2018;Kraljic et al 2020b), others (Ganeshaiah Veena et al 2019;Krolewski et al 2019) found preferential perpendicular orientation with respect to filaments at all masses with no sign of a spin transition. A possible interpretation of this lack of detection of a clear transition is the nature of the filaments, with galaxies in thinner filaments having their spins more likely perpendicular to the filament's axis, compared to galaxies of similar mass in thicker filaments (Ganeshaiah Veena et al 2019).…”
Section: Introductionmentioning
confidence: 92%
“…The mass dependence of the spin alignment signal is however debated. While some works confirmed the existence of a galaxy spin transi- tion from parallel to perpendicular with respect to the filament's direction (Dubois et al 2014;Codis et al 2018;Kraljic et al 2020b), and analogously with respect to walls (Codis et al 2018;Kraljic et al 2020b), others (Ganeshaiah Veena et al 2019;Krolewski et al 2019) found preferential perpendicular orientation with respect to filaments at all masses with no sign of a spin transition. A possible interpretation of this lack of detection of a clear transition is the nature of the filaments, with galaxies in thinner filaments having their spins more likely perpendicular to the filament's axis, compared to galaxies of similar mass in thicker filaments (Ganeshaiah Veena et al 2019).…”
Section: Introductionmentioning
confidence: 92%
“…The BG effect [58][59][60][61] induces a temperature dipole, of a magnitude comparable to that of the rkSZ effect, with a decrease in CMB temperature following the galaxies' transverse proper motion (and a temperature increase opposite to the transverse proper motion). Regardless of the presence of systematic alignments between the directions of galaxies' spins and their proper motionsinduced, for instance, by filaments [57,[62][63][64]]-, we don't expect any systematic alignment in their sense. Thus, on spin-aligned stacks of large samples of galaxies, any BGinduced temperature dipole should average to zero.…”
Section: Detection Feasibilitymentioning
confidence: 92%
“…Subsequent work by Dubois et al (2014); Welker et al (2014); Codis et al (2018); showed a clear mass-dependent spin transition of galaxies from parallel to perpendicular in the Horizon AGN and Illustris hydro simulations. In contrast, Ganeshaiah Veena et al (2019) and Krolewski et al (2019) detected a mass dependent alignment but not a spin transition in SPH based EAGLE and Massive Black-2 simulations. Apart from galaxy stellar mass, the spin alignment trend depends on galaxy morphology (Wang & Kang 2017;Ganeshaiah Veena et al 2019), color (Codis et al 2018;, HI content and filament density (Kraljic, Davé & Pichon 2020).…”
Section: Galaxy Spin Alignmentsmentioning
confidence: 84%
“…The first robust observational evidence was provided by the Tempel, Stoica & Saar (2013) and Tempel & Libeskind (2013b) who have shown that the spins of spiral galaxies are preferentially aligned with the filament axis while the minor axis of elliptical galaxies, which are typically higher mass, is preferentially perpendicular to the filaments axis (see also Jones, van de Weygaert & Aragón-Calvo 2010; Hirv et al 2017). The same trend, although at a lower statistical significance due to the smaller sample, is seen when inferring the spin from the stellar or gaseous velocity maps, such as those obtained using SAMI or MaNGA (Krolewski et al 2019;Welker et al 2020;Blue Bird et al 2020) The present day alignment between halo and galaxy spin and their filaments is different from that predicted by TTT. For example, as we just discussed, the high-mass haloes have a propensity for perpendicular spin while TTT predicts a parallel alignment.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation